Antimicrobials associated adverse drug reaction profiling: a four years retrospective study (Pharmacovigilance study). Issue 1 (1st January 2021) - Agrawal, Manju; Singh, Preeti; Joshi, Usha
ABSTRACT: Background: All drugs profoundly modify our biological processes and may manifest as adverse drug reactions (ADRs), which are unpredictable and inevitable consequences. Antibiotics are a common cause of ADR, necessitating stopping or change of antibiotics. The incidence of ADRs increases with the number of drugs prescribed in a prescription, and antibiotics are rarely prescribed as monotherapy. Aim: The study aimed to assess frequency, class of antibiotics, symptoms, causality, the severity of antimicrobial-associated ADRs, and see the demographic distribution. Methods: ADRs were collected and filled in suspected ADR forms and sent via vigiflow to the National Coordination Centre-Pharmacovigilance Programme of India (NCC-PvPI). These ADR reports, termed individual case safety reports (ICSRs), were analyzed from Jan 2016 to Dec 2019. Results: A total of 414 (54.33%) ICSRs of 762 were identified as antimicrobial-associated. Adults in the age group 19–65 years accounted for 345 (83.09%) of ADRs. A total of 192 (46.38%) were males, and 222 (53.14%) were females. Skin and subcutaneous tissue System organ class was involved in 54% of cases. In the causality assessment, 268 (64.49%) were "probable, " 123 (29.71%) were "possible, " and 23 (5.56%) were "certain." On severity assessment, 256 ADRs (61.83%) were mild, 133 (32.12%) were moderate, and 25 (6.03%) were severe. A total of 54 antimicrobial agents, excluding anti-tubercular drugs, were identified, and antibacterial accounted for 268 (64.73%) ADRs, followed by antiviral 90 (21.73%), antiprotozoal agents 33 (7.97%) antimalarials anti-scabicidal, antifungal accounting for the remaining. Conclusion: Antimicrobials play a crucial role in treating infections, and utmost vigilance during antimicrobials prescription reduces the frequency and severity of the ADRs, thereby reducing the morbidity and mortality and the pharmacoeconomic burden to the health care system. Pharmacovigilance must be boosted to ensure the safe and effective use of antibiotics and reduce the occurrence of ADRs.